Posouzení účelnosti zavedení zastávek na znamení na konkrétní lince - Svoboda, Lukáš; Lukáš Svoboda (České vysoké učení technické v Praze, 2020)
Předmětem bakalářské práce „Posouzení účelnosti zavedení zastávek na znamení na konkrétní lince“ je analyzovat současný stav zastávek na znamení MHD v Praze a na základě této analýzy posoudit, zda celoplošné zavedení zastávek (autobusových) na znamení bude mít nějaké kladné ohlasy.

The subject of the thesis „Assessing the effectiveness of establishing request stops on a specific line“ is to analyze the current state of request stops of public transport in Prague and on the basis of this analysis to assess whether the allover implementation of request bus stops will have any positive responses.
Assessment of the Effectiveness of Stops on Signs on a on a Specific Line
Keywords: zastávky na znamení; MHD; autobus; řidič; cestující; request stops; public transport; bus; bus driver; passenger